Efek estetik-seduktif pada multimedia terhadap hasil belajar - Pranata, Moeljadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
Effects of seductive aesthetic in multimedia on learning outcomes. Presenting the message in a seductive aesthetic is common in multimedia learning applications. This study aims to test the effect of the aesthetic message design on learning outcomes. Applied experimental method to compare the effects of message design of aesthetic format (DPS), essential (DPE), redundancy verbal (DPR), aesthetic and redundancy verbal (DPS-R) against the results learning of 2 groups different literacy. Analysis of data using MANOVA with significance level 0.05. DPE presentation proved the most superior in learning retention and transfer. Presentation DPS produces a higher transfer on the subject that have a visual rather than verbal literacy. The results of this study suggest that it should give priority to multimedia design theories are based on dual coding of memory than the aesthetic theories of learning when the goals are directed to maximize the transfer capability.